2016
DOI: 10.1016/j.marpol.2016.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the added value of the recent declaration on unregulated fishing for sustainable governance of the central Arctic Ocean

Abstract: The 'Declaration concerning the prevention of unregulated high seas fishing in the central Arctic Ocean' signed by the Arctic 5 nations, limits unregulated high seas fishing in the central part of the Arctic Ocean, and holds potential social, economic and political impacts for numerous stakeholders. In this paper, the four Interim Measures in the Declaration are discussed and what value these measures bring beyond the existing international agreements is explored. It is found that even though the Declaration f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 31 publications
(19 reference statements)
0
12
0
Order By: Relevance
“…The Arctic5-Declaration bans unregulated fishing within the 2.8 million km2 area of the CAO and is a precautionary measure as no large scale commercial fishing is expected in this region in the nearest future. In addition, the declaration has implications for joint international scientific research [45,46].…”
Section: Boxmentioning
confidence: 99%
See 4 more Smart Citations
“…The Arctic5-Declaration bans unregulated fishing within the 2.8 million km2 area of the CAO and is a precautionary measure as no large scale commercial fishing is expected in this region in the nearest future. In addition, the declaration has implications for joint international scientific research [45,46].…”
Section: Boxmentioning
confidence: 99%
“…Currently, no regional fisheries management platform exists for most of the CAO, and unless property rights and responsibilities are resolved, it will be difficult to initiate one. It has been suggested that the CAO could be included in an already existing RFMO, e.g., the North-East Atlantic Fisheries Commission (NEAFC) or that new "RFMO-type" collaboration could be developed [46] in case commercial fishing moves to this region. The RFMOs host intergovernmental dialogue around issues relevant to the UNCLOS Straddling Fish Stocks Agreement and hence they are important structures for sustainable high seas fisheries management.…”
Section: Fisheries Management In a Cross-scale Worldmentioning
confidence: 99%
See 3 more Smart Citations